The Rise of Tower Provider (What Factors Impact Company’s Performance?) - Pradono, Noel Singgih Haryo (KINERJA, 2019)
This study aims to determine the effect of Tenants, Financial Leverage, Foreign Owned Subsidiary and institutional shareholder on company’s performance. The population consist of tower provider company listed on Indonesia Stock Exchange and we use time period of 2012 – 2017. Using purposive sampling method, we acquired five companies nonrelated to each other until 2017. We used Eviews 7 to conduct panel data regression statistic. The result showed that only institutional shareholder significantly impacts company’s performance.